2019
DOI: 10.32583/pskm.9.3.2019.233-240
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Pengetahuan Dan Motivasi Dengan Perilaku Ibu Hamil Menggunakan Kosmetik Pemutih

Abstract: Fenomena penggunaan kosmetik pemutih Non-BPOM oleh ibu hamil masih banyak di lakukan karena sebagian mereka menganggap itu sebagai kebutuhan yang memang harus dilakukan. Tidak hanya itu saja tapi penggunaan kosmetik pemutih Non-BPOM oleh ibu hamil juga di lakukan karena adanya rendahnya pengetahuan akan dampak dan kandungan kosmetik dan masih tingginya motivasi ibu hamil untuk mempercantik diri. Tujuan penelitian ini untuk mengetahui hubungan  pengetahuan dan motivasi dengan perilaku ibu hamil menggunakan kosm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
12

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 2 publications
0
4
0
12
Order By: Relevance
“…Good knowledge of the dangers of smoking may not necessarily change smoking behavior or habits, especially if someone's knowledge is not good/low it causes the possibility of causing someone's attitude to smoke higher in this study it is proven that the low knowledge of respondents results in many respondents' attitudes positive/negative to smoking These results are in line with research conducted by Budiyati in 2021 concerning knowledge, attitudes and smoking behavior in adolescents, where the results showed that 56.7% of adolescents had a bad attitude towards smoking. In Budiyati's research, it was stated that even though adolescents had good knowledge about smoking, it did not guarantee that attitudes would also be good (Budiyati et al, 2021). In addition to knowledge, attitude is also influenced by perception, knowledge, and perception can affect one's assessment of smoking habits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Good knowledge of the dangers of smoking may not necessarily change smoking behavior or habits, especially if someone's knowledge is not good/low it causes the possibility of causing someone's attitude to smoke higher in this study it is proven that the low knowledge of respondents results in many respondents' attitudes positive/negative to smoking These results are in line with research conducted by Budiyati in 2021 concerning knowledge, attitudes and smoking behavior in adolescents, where the results showed that 56.7% of adolescents had a bad attitude towards smoking. In Budiyati's research, it was stated that even though adolescents had good knowledge about smoking, it did not guarantee that attitudes would also be good (Budiyati et al, 2021). In addition to knowledge, attitude is also influenced by perception, knowledge, and perception can affect one's assessment of smoking habits.…”
Section: Discussionmentioning
confidence: 99%
“…There are 4000 chemicals contained in one cigarette that can harm health, the three most dangerous ingredients are carbon monoxide, nicotine, and tar (Budiyati et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Lebih dari separuh responden (59%) memiliki sikap mendukung dalam merokok seperti banyaknya yang tidak setuju (38 responden) untuk tidak merokok daripada menciptakan citra yang buruk dilingkungannya. Sikap merupakan respon seseorang terhadap perilaku, sikap terhadap merokok merupakan pendapat sesorang terhadap bagaimana merokok tersebut yang terbentuk dari kesedian dan dipengaruhi oleh emosi yang dapat dilihat dari perbuatan yang dilakuakan atau kebiasaan yang dilakukan (Budiyati et al, 2021).…”
Section: Hasil Dan Pembahasan Gambaran Deskripsi Variabel Penelitianunclassified
“…Merokok membawa berbagai bahaya bagi perokok dan orang sekitar. Terdapat 4000 bahan kimia yang terkandung dalam satu batang rokok dapat membahayakan kesehatan, tiga kandungan yang paling berbahaya adalah karbon monoksida , nikotin dan tar (Budiyati et al, 2021).…”
unclassified
“…3 Pemakaian krim pemutih yang mengandung bahan berbahaya dapat berdampak pada janin seperti kecacatan pada janin, keguguran, kembar siam, jari dempet, dan bibir sumbing. 6 Masalah kulit akibat pemakaian produk pencerah, sebagian besar mengalami pengelupasan kulit (, 59.1%), jerawat (, 40.9%), dan gatal (, 36.4%). Hanya 22,7% () responden (3 mahasiswa pascasarjana dan 2 mahasiswa) pernah berkonsultasi dengan dokter jika mengalami masalah kulit.…”
Section: Hasil Karakteristik Respondenunclassified